FRI0443 CLINICAL CHARACTERISTICS AND RELATED FACTORS OF COMMON RHEUMATIC DISEASES COMPLICATED WITH TUBERCULOSIS INFECTION. (2nd June 2020) - Long, L.; Tang, G.; Han, Y.; Peng, Q.; Liu, J.; Chen, X.; Zhou, Q.
Abstract : Background: Rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and syndrome(SS) are common rheumatic diseases with high incidence. Patients with those rheumatic diseases are at high risk of tuberculosis (TB) infection. However, manifestations can be atypical and easily confused with those of rheumatic disease itself. For those patients, diagnosis is usually much more difficult and further make treatment delayed. Sometimes it may lead to mistreatment. Therefore, it is important to recognize the clinical characteristics of those patients. Objectives: To explore the clinical characteristics and high risk factors of common systemic rheumatism complicated with tuberculosis infection. Methods: A total of 3, 906 cases of RA, SLE, and SS common systemic rheumatism diagnosed in the People's Hospital of Sichuan Province from January 2007 to January 2017 were collected with carefully exclusion with other infectious diseases and neoplastic disease. One hundred and five patients with TB were included as infection group, including 42 cases of RA, 41 cases of SLE, and 22 cases of SS. In the control group, 84 patients with RA, 82 patients with SLE, and 44 patients with SS were randomly selected from the corresponding rheumatoid non-infected patients hospitalized during the same period. Results: Fever was the most common symptom among 42 cases of RA, 41 cases of SLE, and 22 cases of SS with TB, accounting for 83.3%, 92.7%, and 68.2%, respectively. Cough, weight loss or fatigue was less common. For 41 cases of SLE and 22 cases of SS with TB, the proportion of pulmonary was 46.3%, 59.01%, respectively.In TB infection group, 27 cases of RA, 21 cases of SLE, and 13 cases of SS with TB had two or more chest CT findings, accounting for 59%, 57%, 62%, respectively. Lesions located in the posterior or posterior segment which TB usually affected were 9 cases(33.3%), 9cases(42.9%), 6cases(27.2%), respectively.The daily average dose of hormones within 1 year in TB infection group was higher than that in the control group (P<0.05). For SLE patients, lower counts of CD4+TL were found in TB infection group (P<0.05), while no such differences were found in RA and SS group. Conclusion: Patients with RA who have TB infection are mainly pulmonary TB. For SLE and SS patients, the chance of pulmonary tuberculosis and extra-pulmonary tuberculosis is similar.Symptoms of RA, SLE, SS with TB, such as fever, cough, weight loss, fatigue, are similar with the primary disease or other infection. Chest imaging is diversity. It is difficult to diagnose.Daily average dose of hormone within one year may be a common risk factor for RA, SLE and SS patients with TB. Decreased CD4+TL may also be a risk factor for SLE patients with TB. References: [1]Cantini F, Nannini C, Niccoli L, et al. Risk of Tuberculosis Reactivation in Patients with Rheumatoid Arthritis, Ankylosing Spondylitis, and Psoriatic Arthritis Receiving Non-Anti-TNF-Targeted Biologics[J]. Mediators of Inflammation, 2017, 2017(6):1-15. [2]Ruangnapa K, Dissaneewate P, Vachvanichsanong P. Tuberculosis in SLE patients: rare diagnosis, risky treatment.[J]. Clinical & Experimental Medicine, 2015, 15(3):429-432. [3]Manuela D F, Bruno L, Martina S, et al. Lung Infections in Systemic Rheumatic Disease: Focus on Opportunistic Infections[J]. International Journal of Molecular Sciences, 2017, 18(2):293-315. [4]Disseminated tuberculosis masquerading as a presentation of systemic lupus erythematosus.Li JC, Fong W, Wijaya L, Leung YY.Int J Rheum Dis. 2017 Oct 2. doi: 10.1111/1756-185X.13195. [5]Handa R, Upadhyaya S, Kapoor S, et al. Tuberculosis and biologics in rheumatology: India – A special situation[J]. International Journal of Rheumatic Diseases, 2017, 51(2):115. Disclosure of Interests: None declared